The Moment the Border is Crossed: The Moment the Border is Crossed (AmeriQuests)
By way of introduction to this issue, which features work by Thomas Spijkerboer that investigates parallels between evictions of irregularized persons in Apartheid South Africa and contemporary Europe, as well as a portfolio of commentaries and a set of book reviews on current work in the field, Robert Barsky offers a  reflection on a new project aimed at studying the first few minutes of an encounter between vulnerable migrants and a host country officials.